The Portuguese Charter of Human Rights in the Digital Age - Domingos Miguel Soares Farinho (Asociación Española de Acreditación de la Transparencia, 2021)
The paper carries out a legal appraisal of the recently approved Portuguese Charter of Human Rights in the Digital Age. It analyses its structure both as a human rights instrument and as Portuguese fundamental rights instrument focusing on new norms introduced in the system and redundant ones. In this latter case interpretation problems are highlighted, in particular when considering the Portuguese open clause of Article 16 of the Constitution that allows for fundamental rights approved by ordinary laws.  Finally, a specific new right is given special attention - the right to protection against disinformation – especially concerning its relation with the freedom of expression. The paper aims to show that the scope of the new provision would allow an unconstitutional restriction on the freedom of expression and that a valid norm must be determined by adequate balancing.